Penguatan Literasi Konfigurasi Jaringan Dasar pada Siswa SMA Annida melalui Praktik Bridge dan DHCP berbasis MikroTik RouterOS - Abdurrasyid Abdurrasyid; Meilia Nur Indah Susanti; Rahmad Evan; Indrianto Indrianto (Politeknik Piksi Ganesha Indonesia, 2026)
Digital-based learning in schools requires local network infrastructure that is not only connected but also properly configured and technically verifiable. However, at the student level, understanding of computer networks is often limited to using internet services without mastering basic configuration concepts such as IP addressing, gateway configuration, and automated IP distribution mechanisms. This community service activity aims to strengthen basic network configuration literacy among students at MTs Annida through structured practice of bridge and Dynamic Host Configuration Protocol (DHCP) configuration using MikroTik RouterOS. The implementation method adopts a Diagnosa Demonstrasi rill Debrief approach, which includes identifying students’ initial understanding, demonstrating configuration procedures, conducting structured hands-on practice, and reflecting on the results of the activities. The practical scenario covers creating a bridge, combining multiple LAN ports into a bridge interface, assigning an IP gateway to the bridge interface, configuring an address pool, activating the DHCP server, and verifying the client side through checking IP address, gateway, DNS, and connectivity tests. The evaluation was conducted using a pre-test and post-test design along with performance-based assessment using a rubric. The results show an increase in the average score from 51.63 to 74.63, indicating an improvement of approximately 44.5% after the training. Furthermore, students’ configuration skills improved as evidenced by successful technical verification during the practical activities. These findings indicate that practice-based network configuration learning is effective in improving students’ literacy and basic skills in computer networking.